44.6k views
5 votes
Consider the following initial-value problem. (x + y)2 dx + (2xy + x2 − 2) dy = 0, y(1) = 1 Let ∂f ∂x = (x + y)2 = x2 + 2xy + y2. Integrate each term of this partial derivative with respect to x, letting h(y) be an

User Jack Guo
by
4.6k points

1 Answer

4 votes


(x+y)^2\,\mathrm dx+(2xy+x^2-2)\,\mathrm dy=0

Suppose the ODE has a solution of the form
F(x,y)=C, with total differential


(\partial F)/(\partial x)\,\mathrm dx+(\partial F)/(\partial y)\,\mathrm dy=0

This ODE is exact if the mixed partial derivatives are equal, i.e.


(\partial^2F)/(\partial y\partial x)=(\partial^2F)/(\partial x\partial y)

We have


(\partial F)/(\partial x)=(x+y)^2\implies(\partial^2F)/(\partial y\partial x)=2(x+y)


(\partial F)/(\partial y)=2xy+x^2-2\implies(\partial^2F)/(\partial x\partial y)=2y+2x=2(x+y)

so the ODE is indeed exact.

Integrating both sides of


(\partial F)/(\partial x)=(x+y)^2

with respect to
x gives


F(x,y)=\frac{(x+y)^3}3+g(y)

Differentiating both sides with respect to
y gives


(\partial F)/(\partial y)=2xy+x^2-2=(x+y)^2+(\mathrm dg)/(\mathrm dy)


\implies x^2+2xy-2=x^2+2xy+y^2+(\mathrm dg)/(\mathrm dy)


\implies(\mathrm dg)/(\mathrm dy)=-y^2-2


\implies g(y)=-\frac{y^3}3-2y+C


\implies F(x,y)=\frac{(x+y)^3}3-\frac{y^3}3-2y+C

so the general solution to the ODE is


F(x,y)=\frac{(x+y)^3}3-\frac{y^3}3-2y=C

Given that
y(1)=1, we find


\frac{(1+1)^3}3-\frac{1^3}3-2=C\implies C=\frac13

so that the solution to the IVP is


F(x,y)=\frac{(x+y)^3}3-\frac{y^3}3-2y=\frac13


\implies\boxed{(x+y)^3-y^3-6y=1}

User Ruslan Mushkaev
by
4.8k points